The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.4067/s0716-97602003000300013
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of the coding regions of the heat shock proteins HSP10 and HSP16 from Piscirickettsia salmonis

Abstract: Piscirickettsia salmonis is an obligate intracellular pathogen that causes the salmonid rickettsial septicemia (SRS) (Branson and Nieto Díaz-Muñoz, 1991; Lannan and Fryer, 1993; Fryer and Mauel, 1997). This disease causes high mortality i n s a l m o n i d s i m p a c t i n g h e a v i l y t h e salmoniculture industry in Chile, where this bacterium was originally isolated. P. salmonis has also been identified in Norway (House et al., 1999), Scotland and Canada (Brocklebank et al., 1993; Jones et al., 1998). U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The amounts of PoHSP40B6 and PoHSP40B11 mRNA transcripts remained unchanged Dong et al (2006) recombinant proteins made (Wilheim et al 2003). A rabbit serum against P. salmonis total protein reacted with prepared recombinant heat shock proteins and similar reactivity was found with serum from salmon infected with P. salmonis demonstrating a fish immune response against bacterial HSP.…”
Section: Effects Of Disease On Fish Hsp Regulation and Expressionmentioning
confidence: 57%
“…The amounts of PoHSP40B6 and PoHSP40B11 mRNA transcripts remained unchanged Dong et al (2006) recombinant proteins made (Wilheim et al 2003). A rabbit serum against P. salmonis total protein reacted with prepared recombinant heat shock proteins and similar reactivity was found with serum from salmon infected with P. salmonis demonstrating a fish immune response against bacterial HSP.…”
Section: Effects Of Disease On Fish Hsp Regulation and Expressionmentioning
confidence: 57%
“…It has been suggested that HSP10 and HSP16 of P. salmonis are highly immunogenic in salmon and are thus bona fide antigens for inclusion in an experimental vaccine to control piscirickettsiosis (Wilhelm et al . ). Subsequently, recombinant HSP60 and HSP70 from P. salmonis were shown to elicit a humoral response when injected intraperitoneally into Atlantic salmon and conferred protection on fish challenged with P. salmonis (Wilhelm et al .…”
Section: Prevention and Controlmentioning
confidence: 97%
“…Interestingly, a sequence analysis of ChaPs has demonstrated that the protein is an HSP, which is a type of molecule that has already been identified and exploited in recombinant vaccine development (Wilhelm et al . ).…”
Section: Prevention and Controlmentioning
confidence: 97%